Divine revelation in the Judeo-Christian tradition - Morcov, Elena (Technium Social Sciences Journal, 2023)
The fundamental idea of ​​God's revelation to people is expressed from a theological and semantic perspective through the concept of Revelation. The revelation of the Old Testament must be interpreted in a missionary vision with a universal character, especially when it comes to the fields of theology, anthropology, and ecclesiology. Here, messianism, that is, the expectation of God's salvation for all peoples, finds fulfillment in the historical context. The Old Testament is presented as the main way God communicated with the patriarchs and prophets using various means. This communication was achieved through theophanies, that is, visible manifestations of His presence in the form of phenomena such as fire or wind, but also through dreams, visions and by supporting the Israelites in their liberation from Egypt and in the conquest of the promised land.